Racismo e justiça ocupacional: construção de identidade e engajamento ocupacional de mulheres negras quilombolas - Pereira, Amanda dos Santos (Universidade Federal de São Carlos, 2022)
Since Brazil's imperial era, enslaved black Africans have sought ways to resist the horrors of slavery. The groups that brought together these individuals received the name of quilombos, a word of origin in the Bantu language, which means settlement or fortress. The communities of quilombos in Brazil live in situation of economic and social vulnerability, being victims of exclusion, discrimination and poverty. These inequalities prevent black women from engaging in occupations they consider significant. Meaningful occupations are purposeful actions which are motivated by interest and will. This study aims to understand how racism interferes in the construction of identity and in the occupational engagement of black quilombola women. The study aims to 1. Describe the significant occupations performed by black quilombola women; 2. Identify women's perceptions and feelings about the experience of racism; 3. Understand the influence of deprivation of occupational engagement in the lives of black quilombola women; 4. Identify the coping strategies eventually used by this group against racist stereotypes. This is a study with a qualitative approach associated with visual methodologies, using photovoice as a data generation instrument, in addition to interviews and participant observation. Data were obtained from narratives and photos produced by nine black women who reside in the quilombola community called Comunidade da Pinguela, located in the countryside of Bahia. Data were analyzed using thematic analysis which resulted in five categories. Category I: Quilombola identity and occupational identity: The ambivalence between pride and shame: the deprivation of occupational engagement outside the quilombo. Category II: Quilombola Resistance: Struggles against invisibility, disputes over territory, difficulties of capitalism, violation of rights, dissatisfaction with federal government policies and inefficient public security. Category III: From black ancestry to the 21st century: Chosen amnesia from historical oppression, black diaspora, ancestral traditions and religious syncretism. Category IV: Racism and occupational injustice: Feelings, perceptions and strategies for overcoming racist stereotypes. Category V: The insurgency of quilombola women: Sisterhood and gender disparity in occupations. Through the results, the main issues experienced by women in their daily lives were shown, such as the care they have with the community, social relationships based on solidarity and sisterhood, how they build their identities and the assigned meanings, the struggle against invisibility, violation of rights and silencing, among other aspects. The study shows that research involving the quilombola population, therapy and occupational science is scarce, and opportunities for professional training and interventions in this field are also rare. Thus, I suggest ways of coping with these tensions, reflecting on the peculiarities of therapy and occupational science for research, teaching and the provision of relevant services to these populations. In addition, the study reaffirms the urgent need to implement public policies that recognize and respect the values ​​and rights of the Brazilian quilombola population.
Racism and occupational justice: identity construction and occupational engagement of black quilombola women
Keywords: Mulher negra; Quilombo; Terapia ocupacional; Racismo; Territórios contestados; Black woman; Occupational therapy; Racism; Contested territories; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL